Time Optimization for Radius Updates in Zone Dynamics of Zone Routing Protocol - Muhsin Bayu Aji Fadhillah; Radityo Anggoro (Universitas Muhammadiyah Malang, 2020)
Vehicular ad hoc networks are wireless network technologies that can be used to communicate without the need for fixed infrastructure. The use of zone routing protocol which is a hybrid routing protocol in a vehicular ad hoc network environment can reduce delay, packet flooding, and excess bandwidth usage on the network. However, traditional zone routing protocol is only configured for one fixed radius value, which makes it not adapt to existing network conditions. Zone dynamics with adaptive radius values in zone routing protocol are used so that zones formed by nodes are more optimal. In adapting the radius value to make the zone dynamics necessary, the optimal configuration of the radius update time is required. Simulations and tests that have been carried out with NS-2 show that the proper update time can improve zone routing protocol performance with a low end-to-end delay and routing overhead value, but has a high packet delivery ratio.